The Effect Of Taxation Socialization, Taxation Knowledge, And Service Quality On Corporate Taxpayer Compliance With Taxpayer Awareness As An Intervening Variable At KPP Pratama Selatan Batam City - Mercy Reyne Marlina Tirayoh; Bambang Satriawan; Robin Robin (International Journal of Management Research and Economics, 2023)
The impact of several changes in the tax law also requires the socialization of taxation to the community so that tax awareness and taxpayer compliance can also increase. Taxpayers will underreport their taxes when their tax obligations are uncertain but this possibility can be reduced if the tax office or agency can provide low-cost information to taxpayers. One of the efforts to provide tax information to the public and taxpayers is through tax socialization activities. The purpose of this study is to determine and analyze the effect of taxation socialization, taxation knowledge, and service quality on taxpayer compliance directly or mediated by taxpayer awareness of the nature of testing the relationship between variables. The research population was 14,483 corporate taxpayers registered at KPP Pratama Batam Selatan with sampling techniques using the Slovin formula with a leeway of 9% obtained a sample of 123 people. The data analysis technique uses path analysis techniques with the help of statistical tools PLS Ver. 3. The results of data analysis obtained socialization of taxation, taxation knowledge, and service quality have a direct effect with a significance value below 0.05 on taxpayer awareness. the socialization of taxation, taxation knowledge, service quality, and taxpayer awareness have a direct effect with a significance value below 0.05 on taxpayer compliance. The results of the indirect effect obtained by tax socialization, tax knowledge, and service quality have an indirect effect with a significance value below 0.05 on taxpayer compliance through taxpayer awareness.